Hubungan Pengetahuan dan Sikap terhadap Pola Penggunaan Obat Tradisional untuk Swamedikasi di Masyarakat Kota Denpasar - Ni Made Maharianingsih (Indonesian Journal of Pharmaceutical Education, 2023)
The behavior of self-medication in Indonesian society is quite large and one of the classes of drugs that can be used for self-medication is traditional medicine. The use of traditional medicine is influenced by the knowledge and attitudes of the community. This research aims to determine the relationship between knowledge and attitudes towards patterns of use of traditional medicine for self-medication in the community in Denpasar City. The research method used was an observational analytic cross-sectional study. The location used in this study is the city of Denpasar, with the time of the study taking place in July-September 2020. The research subjects are people who live in Denpasar City aged 20-64 years who buy and use traditional medicines with a total of 400 people. Data were collected by distributing questionnaires to research subjects to measure knowledge, attitudes, and patterns of use of traditional medicines. The results obtained were the pattern of self-medicated traditional medicine in most of the community with the frequency of using drugs more than 4 times a month (23.25%), the most common complaints were headaches (32.5%), the type of traditional medicine was the branded herbal medicine class %), the effect that was felt from the use of traditional medicine was getting better (98.5%) with no side effects (87.25%). Most of the information sources of traditional medicine were from the family (50.25%). Knowledge and attitudes of the people of Denpasar city are mostly classified as high with a percentage of 67.25% for knowledge and 65.50% for attitudes. It can be concluded that there is a significant or moderate relationship between knowledge and the respective patterns of use of traditional medicines, except for the relationship between attitudes and low or weak prices of traditional medicines.